Closure of gastrointestinal defects with Ovesco clip: long-term results and clinical implications. (September 2016) - Donatelli, Gianfranco; Cereatti, Fabrizio; Dhumane, Parag; Vergeau, Bertrand Marie; Tuszynski, Thierry; Marie, Christian; Dumont, Jean-Loup; Meduri, Bruno
Background: The Over-The-Scope Clip (OTSC®, Ovesco Endoscopy GmbH, Tübingen, Germany) is an innovative clipping device that provides a strong tissue grasp and compression without provoking ischemia or laceration. In this retrospective study we evaluated immediate and long-term success rates of OTSC deployment in various pathologies of the gastrointestinal (GI) tract. Methods: A total of 45 patients (35 female, 10 male) with an average age of 56 years old (range, 24–90 years) were treated with an OTSC for GI defects resulting from a diagnostic or interventional endoscopic procedure (acute setting group) or for fistula following abdominal surgery (chronic setting group). All procedures were performed with CO2 insufflation. Results: From January 2012 to December 2015 a total of 51 OTSCs were delivered in 45 patients for different kinds of GI defects. Technical success was always achieved in the acute setting group with an excellent clip adherence and a clinical long-term success rate of 100% (15/15). Meanwhile, considering the chronic setting group, technical success was achieved in 50% of patients with a long-term clinical success of 37% (11/30); two minor complications occurred. A total of three patients died due to causes not directly related to clip deployment. Overall clinical success rate was achieved in 58% cases (26/45 patients). A mean follow-up period of 17 months was accomplished (range, 1–36 months). Conclusion: OTSC deployment is an effective and minimally-invasive procedure for GI defects in acute settings. It avoids emergency surgical repair and it allows, in most cases, completion of the primary endoscopic procedure. OTSC should be incorporated as an essential technique of today's modern endoscopic armamentarium in the management of GI defects in acute settings. OTSCs were less effective in cases of chronic defects.